Steel rail flash welding joint microcell hydrogen damage test method

By performing micro-zone division, sampling, nickel plating and hydrogen permeation tests on the rail flash welding joints, the degree of hydrogen damage in each micro-zone is accurately evaluated, and the problem of difficulty in detecting hydrogen damage in the micro-zone in the prior art is solved, and the welding quality and railway transportation safety are improved.

CN119959125AInactive Publication Date: 2025-05-09SOUTHWEST JIAOTONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510447836.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-10
Publication Date
2025-05-09
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to accurately detect hydrogen damage in the micro-zone of the rail flash welded joint, which causes the strength, toughness and fatigue performance of the welded joints to be affected, which in turn affects the service life of the rail and the safety of railway operation.

Method used

By dividing the rail flash welded joint into four micro zones (weld area, complete normalizing area, incomplete normalizing area and parent material area), each micro zone was subjected to linear cutting sampling, nickel plating treatment and hydrogen permeation test under the dual electrolytic cell device, the apparent hydrogen diffusion coefficient, hydrogen flux and hydrogen permeability concentration were calculated, and the degree of hydrogen damage in each micro zone was evaluated.

Benefits of technology

Accurate assessment of hydrogen damage in the micro-zone of rail flash welding joints has been achieved, the welding quality has been improved, and the safety of railway transportation has been ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119959125A_ABST
    Figure CN119959125A_ABST
Patent Text Reader

Abstract

The invention discloses a steel rail flash welding joint microcell hydrogen damage testing method, and relates to the technical field of hydrogen damage testing. The test method comprises the following steps: S1, obtaining a target steel rail flash welding head, and dividing the target steel rail flash welding head into four micro-regions; s2, linear cutting sampling is carried out on the target steel rail flash welding heads of the different micro-areas, samples of the different micro-areas are obtained, and the micro-area structure morphology of each sample is obtained; s3, nickel plating treatment is conducted on all the samples, and nickel-plated samples are obtained; s4, performing a hydrogen permeation test on the nickel-plated sample under a double-electrolytic tank device by adopting a constant current method to obtain a hydrogen permeation curve of the current density changing along with the hydrogen charging time in the test process; s5, calculating an apparent hydrogen diffusion coefficient, a hydrogen flux and a hydrogen permeation side hydrogen concentration; and S6, evaluating the hydrogen damage of different micro-area samples. According to the invention, the micro-zone hydrogen damage of the steel rail flash welding joint can be accurately tested, and technical support is provided for guaranteeing railway transportation safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen damage testing, and in particular to a method for testing micro-area hydrogen damage in a rail flash weld joint. Background Art

[0002] As an important part of the railway transportation system, the quality of rails is directly related to the safety and efficiency of railway transportation. With the rapid development of the railway industry, especially the construction of high-speed railways and heavy-duty railways, extremely stringent requirements have been placed on the performance and welding quality of rails. In the rail welding process, flash welding has become one of the most widely used welding methods due to its advantages such as high efficiency and reliability. However, in the flash welding process, the sources of hydrogen in the rails are many and complex. First, in the flash burning stage, the liquid bridge blasting cannot completely isolate the moisture in the environment, and the high temperature will also cause water to decompose into hydrogen, resulting in the introduction of hydrogen atoms. Secondly, the welding process parameters will also affect the hydrogen content. When the welding current is too large and the welding speed is too fast, the cooling speed of the molten pool will be accelerated, and hydrogen will not have time to escape and will remain in the rails. Furthermore, organic matter such as oil in the welding environment will decompose and produce hydrogen during the welding process, which will also be integrated into the rails. In addition, if the deoxidation of the raw materials of the rails is not complete during the smelting process, hydrogen will also remain in the rails in the form of solid solution, hydride, etc. The accumulation of hydrogen in the micro-area of ​​the weld joint can easily cause hydrogen damage, including defects such as hydrogen embrittlement and white spots, which seriously reduce the strength, toughness and fatigue properties of the weld joint, thereby affecting the service life of the rail and the safety of railway operation.

[0003] At present, there are some conventional methods for the quality inspection of rail welding joints, such as appearance inspection, ultrasonic flaw detection, and radiographic flaw detection. These methods can detect macroscopic welding defects, but it is difficult to accurately assess microscopic defects such as micro-area hydrogen damage. For example, in a certain railway trunk line, when the rail flash welding notch specimen was inspected, although the ultrasonic flaw detection showed that it was qualified, it broke after impact. From the fracture analysis, the crack source position is smooth and bright, and the shape is like an eye, showing typical hydrogen-induced cracking characteristics. The investigation found that the rust was not completely removed during rail welding, and the water in the rust decomposed and released hydrogen during the welding process, which remained in the weld. In addition, since the rail welding adopts a sequential solidification method, in order to ensure the quality of the rail working surface, the working surface solidifies first, and some areas become the last solidification position. Hydrogen is "driven" to these parts along the solidification order, causing hydrogen enrichment and eventually causing fracture. The ultrasonic detection used in this accident failed to detect the defect in time because the straight probe is insensitive to cracks parallel to the direction of ultrasonic propagation.

[0004] Micro-area hydrogen damage is hidden and complex. Its impact on the performance of welded joints is not easy to be found in macroscopic detection, but it may gradually appear during the service of rails, causing serious safety accidents. Therefore, developing a method that can accurately test micro-area hydrogen damage in rail flash welds is of great practical significance for improving rail welding quality and ensuring railway transportation safety. Summary of the invention

[0005] In view of the above problems, the present invention aims to provide a method for testing micro-area hydrogen damage of rail flash weld joints.

[0006] The technical solution of the present invention is as follows: A method for testing micro-area hydrogen damage of a rail flash weld joint comprises the following steps: S1: obtaining a target rail flash weld joint, and dividing the target rail flash weld joint into four micro-areas, wherein the four micro-areas include a weld area, a complete normalizing area, an incomplete normalizing area, and a base material area; S2: Wire cutting is performed on the target rail flash weld joints of different micro-regions to obtain samples of different micro-regions, and the micro-region structure morphology of each sample is obtained; S3: performing nickel plating treatment on each sample to obtain a nickel-plated sample; S4: performing a hydrogen permeation test on the nickel-plated sample in a double electrolytic cell device using a constant current method to obtain a hydrogen permeation curve of current density changing with hydrogen charging time during the test; S5: calculating the apparent hydrogen diffusion coefficient, hydrogen flux and hydrogen concentration on the hydrogen permeation side according to the hydrogen permeation curve; S6: Evaluate the hydrogen damage of each different micro-area sample according to the micro-area structure morphology and the apparent hydrogen diffusion coefficient, hydrogen flux and hydrogen concentration on the hydrogen permeation side.

[0007] Preferably, in step S1, when dividing the micro-areas, the weld is used as a reference, and the areas with finer grain structures on both sides of the weld are divided into complete normalizing areas, and the areas with coarser grain structures on both sides of the weld are divided into incomplete normalizing areas, and the side adjacent to the incomplete normalizing area and away from the weld is divided into a base material area; the average grain size of the coarser grain structure is larger than the average grain size of the finer grain structure.

[0008] Preferably, in step S2, an electron backscatter diffraction scanning electron microscope and an optical microscope are used to obtain the microstructure morphology of each sample.

[0009] Preferably, in step S3, the nickel plating treatment of the sample specifically includes the following sub-steps: S31: ultrasonically cleaning the sample in a sodium hydroxide solution, and then washing and drying the sample with deionized water; S32: etching the sample dried in step S31 with a concentrated hydrochloric acid solution, and then washing and drying with deionized water; S33: nickel-plating the sample dried in step S32, and then washing and drying with deionized water to obtain the nickel-plated sample.

[0010] Preferably, in step S31, the concentration of the sodium hydroxide solution is 80 g / L, and the ultrasonic cleaning treatment time is 3 min; in step S32, the acid etching temperature is 45° C., and the acid etching time is 15 s.

[0011] Preferably, in step S33, when nickel plating is performed, the electroplating solution used includes 260 g / L NiSO4·6H2O, 45 g / L NiCl2·6H2O, and 40 g / L H3BO3, the electroplating temperature is 60 °C, the electroplating time is 10 min, and the plating current density is 3 mA·cm -2 .

[0012] Preferably, in step S4, the dual electrolytic cell device includes an oxidation cell, a hydrogen charging cell, an electrochemical workstation and a constant potential instrument, the oxidation cell and the hydrogen charging cell are both connected to the nickel-plated sample, and the working electrode of the electrochemical workstation and the negative electrode of the constant potential instrument are both connected to the nickel-plated sample; the oxidation cell serves as an anode cell, the platinum electrode therein is connected to the auxiliary electrode of the electrochemical workstation, and the reference electrode therein is connected to the reference electrode of the electrochemical workstation; the hydrogen charging cell serves as a cathode cell, the platinum electrode therein is connected to the positive electrode of the constant potential instrument.

[0013] Preferably, in step S4, when conducting the hydrogen permeation test, the electrolyte in the oxidation tank is a 4 g / L sodium hydroxide solution, the hydrogen charging liquid in the hydrogen charging tank is a mixed solution of 0.5 mol / L concentrated sulfuric acid and 2 g / L thiourea, and the test current density is 30 mA·cm -2 .

[0014] Preferably, in step S5, the apparent hydrogen diffusion coefficient, hydrogen flux and hydrogen concentration on the hydrogen permeation side are calculated by the following formulae respectively: (1) (2) (3) Where: is the apparent hydrogen diffusion coefficient, cm 2 ·s -1 ; L is the sample thickness, cm; is the lag time, s; is the hydrogen flux, mol·cm-2 ·s -1 ; is the saturated anodic current density, A·cm -2 ; n is the number of electrons transferred; F is the Faraday constant; is the hydrogen concentration on the hydrogen permeation side, mol·cm -3 .

[0015] Preferably, in step S6, when evaluating the hydrogen damage of each different micro-area sample: The greater the apparent hydrogen diffusion coefficient, hydrogen flux and hydrogen concentration on the hydrogen permeation side, the higher the possibility of hydrogen damage; Observe whether there are hydrogen-induced cracks and hydrogen bubbles in the micro-region structure morphology, and calculate the degree of hydrogen damage by the following formula: (4) Where: k is the degree of hydrogen damage; α is the weight of hydrogen-induced cracking; x is the hydrogen-induced crack length, nm; β Weight for hydrogen bubbling; y is the major axis length of the hydrogen bubble ellipse, nm.

[0016] The beneficial effects of the present invention are: The present invention can accurately evaluate the degree of hydrogen damage in a micro-area of ​​a rail flash weld joint, and has important practical significance for improving the quality of rail welding and ensuring railway transportation safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 Schematic diagram of micro-area division of target rail flash weld joint of the present invention; wherein (a) is the appearance profile of the rail; (b) is a schematic diagram of micro-area division; Figure 2 It is a structural schematic diagram of the dual electrolytic cell device of the present invention; Figure 3 For U75V rail base material at 10 mA·cm -2 Schematic diagram of microscopic morphology after hydrogen penetration under current density conditions; Figure 4 For U75V rail base material at 30 mA·cm -2Schematic diagram of microscopic morphology after hydrogen penetration under current density conditions; Figure 5 For U75V rail base material at 100 mA·cm -2 Schematic diagram of microscopic morphology after hydrogen penetration under current density conditions; Figure 6 Schematic diagram of SEM microscopic morphology of each micro-area of ​​a U75V rail joint after hydrogen charging in a specific embodiment; wherein, (a) and (e) are SEM images of the weld area; (b) and (f) are SEM images of the complete normalizing area; (c) and (g) are SEM images of the incomplete normalizing area; (d) and (h) are SEM images of the weld area; Figure 7 Schematic diagram of the first hydrogen charging result of each micro-area of ​​a U75V rail joint in a specific embodiment; wherein (a) is a hydrogen permeation curve; (b) is a normalized curve; Figure 8 Schematic diagram of the second hydrogen charging result of each micro-area of ​​a U75V rail joint in a specific embodiment; wherein (a) is a hydrogen permeation curve; (b) is a normalized curve; Fig. 9 Schematic diagram of the calculation results of the apparent hydrogen diffusion coefficient, hydrogen flux and hydrogen concentration on the hydrogen permeation side of each micro-region of a U75V rail joint in a specific embodiment; wherein (a) is the apparent hydrogen diffusion coefficient; (b) is the hydrogen flux; (c) is the hydrogen concentration on the hydrogen permeation side; Fig.10 Schematic diagram of hydrogen damage morphology of each micro-area of ​​a U75V rail joint in a specific embodiment; wherein (a) is the base material area; (b) is the weld area; (c) is the complete normalizing area; and (d) is the incomplete normalizing area. DETAILED DESCRIPTION

[0019] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that, in the absence of conflict, the embodiments in this application and the technical features in the embodiments can be combined with each other. It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as those generally understood by those of ordinary skill in the art to which this application belongs. The words "including" or "comprising" and the like used in the disclosure of the present invention mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects.

[0020] The present invention provides a method for testing micro-area hydrogen damage of a rail flash weld joint, comprising the following steps: S1: obtaining a target rail flash weld joint, and dividing the target rail flash weld joint into four micro-areas, wherein the four micro-areas include a weld area, a complete normalizing area, an incomplete normalizing area, and a base material area.

[0021] In the present invention, due to the flash welding thermal cycle, the metallographic structure at the weld joint is discontinuous, which will inevitably lead to the performance of the weld joint being dispersed. Therefore, the present invention divides the target rail flash weld joint into four micro-areas: weld area, complete normalizing area, incomplete normalizing area and parent material area, so as to more accurately judge the hydrogen damage of each micro-area.

[0022] In a specific embodiment, Figure 1 As shown, when dividing the micro-areas, the weld is used as a reference, and the areas with finer grain structures on both sides of the weld are divided into complete normalizing areas, and the areas with coarser grain structures on both sides of the weld are divided into incomplete normalizing areas, and the side adjacent to the incomplete normalizing area and away from the weld is divided into the base material area; the average grain size of the coarser grain structure is larger than the average grain size of the finer grain structure.

[0023] Optionally, the area with finer grains (grain size distribution range of 5 to 42 μm, average grain size of about 10 μm) within about 5 to 25 mm on both sides of the weld is divided into a completely normalized area, and the area with coarser grains (grain size distribution range of 10 to 52 μm, average grain size of about 16 μm) within about 25 to 35 mm on both sides of the weld is divided into an incompletely normalized area.

[0024] S2: Wire cutting is performed on target rail flash weld joints of different micro-regions to obtain specimens of different micro-regions, and the micro-region structure morphology of each specimen is obtained.

[0025] In a specific embodiment, electron backscatter diffraction scanning electron microscopy and optical microscopy are used to obtain the microstructure morphology of each sample.

[0026] S3: Perform nickel plating on each sample to obtain a nickel-plated sample.

[0027] In the present invention, by performing nickel plating on the sample, the plated nickel layer can be used to protect the sample, thereby preventing the influence of sample surface oxidation and electrochemical corrosion on the test results of the sample.

[0028] In a specific embodiment, the nickel plating treatment of the sample specifically includes the following sub-steps: S31: ultrasonically cleaning the sample in a sodium hydroxide solution, and then washing and drying the sample with deionized water; S32: etching the sample dried in step S31 with a concentrated hydrochloric acid solution, and then washing and drying with deionized water; S33: nickel-plating the sample dried in step S32, and then washing and drying with deionized water to obtain the nickel-plated sample.

[0029] In the above embodiment, there is grease on the surface of the sample removed by linear cutting. Grease is generally composed of higher fatty acid glycerides. When NaOH comes into contact with grease, a saponification reaction (Formula I) occurs, thereby generating substances such as sodium stearate with good water solubility, thereby removing grease from the surface of the object. When ultrasonic waves propagate in liquid, high-frequency pressure waves are generated, which excite the liquid molecules to vibrate violently to form acceleration. The force generated by the acceleration can impact the oil molecules and cause them to fall off the surface of the cleaned object. The purpose of oil removal is achieved under the combined action of ultrasonic waves and NaOH. After oil removal, the sample is washed and dried with deionized water to ensure that the sample is not contaminated.

[0030] (I) HCl can not only remove the rust on the sample surface (Formula II), but appropriate HCl etching can also make the sample surface rough at the microscopic level and increase the surface area. This allows the plated metal to better adhere to the sample surface during electroplating, increasing the contact area between the plated layer and the sample surface, thereby improving the adhesion and bonding force of the plated layer, and making the plated layer more firmly attached to the sample surface. At the same time, after acid etching, the metal surface is in a highly active state, which is conducive to the reduction and deposition of metal ions on the sample surface during the electroplating process, promoting the electroplating process, and improving the electroplating efficiency and coating quality. After acid etching, use deionized water to wash and dry the sample to ensure that the sample is not contaminated.

[0031] (II) In a specific embodiment, in step S31, the concentration of the sodium hydroxide solution is 80 g / L, and the ultrasonic cleaning treatment time is 3 min; in step S32, the acid etching temperature is 45 ° C, and the acid etching time is 15 s; in step S33, when nickel plating is performed, the electroplating solution used includes 260 g / L NiSO4·6H2O, 45 g / L NiCl2·6H2O, and 40 g / L H3BO3, the electroplating temperature is 60 ° C, the electroplating time is 10 min, and the plating current density is 3 mA·cm -2 .

[0032] In the above embodiment, NiSO4·6H2O is nickel ion (Ni 2+ ) is the main source of. In aqueous solution, NiSO4·6H2O will ionize Ni 2+ and SO4 2- , Ni 2+It is the key ion for reduction and deposition of nickel metal at the cathode during the electroplating process. NiCl2·6H2O is also used to provide nickel ions, increase the concentration of nickel ions in the electroplating solution, and improve electroplating efficiency. It can also be used as an anode activator in rapid nickel plating, which helps dissolve the anode nickel, makes the anode reaction smoother, and ensures the replenishment of nickel ions during the electroplating process. H3BO3 mainly plays a buffering role and can maintain the pH value of the electroplating solution relatively stable. During the electroplating process, some reactions will occur at the cathode and anode that cause changes in the pH value of the solution. Boric acid can add excess OH at the cathode interface. - , preventing the solution pH from rising, inhibiting the formation of nickel hydroxide and other precipitates, so that the electrodeposition reaction can proceed smoothly. Since Pt is an inert electrode, it does not undergo oxidation and dissolution reaction during the electroplating process. When the power is turned on, the anions near the anode (such as SO4 2- etc.) will move toward the anode and react with the OH ionized in the water - Oxidation reaction occurs at the anode (Formula III). The plated part acts as the cathode. Under the action of the electric field, Ni in the plating solution 2+ It moves toward the cathode, obtains electrons on the cathode surface and undergoes a reduction reaction (Formula IV), thereby depositing a layer of nickel metal coating on the surface of the plated part.

[0033] (III) (IV) S4: A hydrogen permeation test is performed on the nickel-plated sample in a double electrolytic cell device using a constant current method to obtain a hydrogen permeation curve of current density changing with hydrogen charging time during the test.

[0034] In a specific embodiment, Figure 2 As shown, the dual electrolytic cell device includes an oxidation cell, a hydrogen charging cell, an electrochemical workstation and a constant potential instrument, the oxidation cell and the hydrogen charging cell are both connected to the nickel-plated sample, and the working electrode of the electrochemical workstation and the negative electrode of the constant potential instrument are both connected to the nickel-plated sample; the oxidation cell serves as an anode cell, the platinum electrode therein is connected to the auxiliary electrode of the electrochemical workstation, and the reference electrode therein is connected to the reference electrode of the electrochemical workstation; the hydrogen charging cell serves as a cathode cell, the platinum electrode therein is connected to the positive electrode of the constant potential instrument.

[0035] In the above embodiment, a three-electrode system is used, in which the metal sample is connected to the working electrode (WE), and the diffusion of hydrogen inside the metal and the reaction on its surface are realized through the working electrode. The reference electrode (RE) provides a stable potential reference for accurately determining the potential change experienced by the working electrode during the hydrogen permeation process, so as to accurately analyze the electrochemical reaction process of hydrogen. The main function of the auxiliary electrode (CE) is to form a loop with the working electrode so that the current can pass through the electrolytic cell smoothly, ensuring the normal progress of the electrochemical reaction, so as to maintain the charge balance of the entire electrolytic cell. The counter electrode usually adopts a material with good conductivity and high chemical stability, such as a platinum electrode (Pt). The hydrogen charging cell and the oxidation cell are responsible for the production and transportation of hydrogen.

[0036] In a specific embodiment, when conducting a hydrogen permeation test, the electrolyte in the oxidation tank is a 4 g / L sodium hydroxide solution, the hydrogen charging liquid in the hydrogen charging tank is a mixed solution of 0.5 mol / L concentrated sulfuric acid and 2 g / L thiourea, and the test current density is 30 mA·cm -2 .

[0037] In the above embodiment, the addition of CH4N2S (thiourea) and H2SO4 in the hydrogen charging cell forms a specific acidic environment. On the surface of the Pt electrode, CH4N2S undergoes an oxidation reaction to produce H + (Formula V), increasing the H + The concentration provides a source for the generation and charging of hydrogen into the sample. CH4N2S can also effectively slow down or even prevent the aggregation of atomic hydrogen into hydrogen molecules and their escape from the cathode surface. At the same time, on the sample surface, the main thing that occurs is H + The reaction of obtaining electrons to generate hydrogen atoms (Formula VI), part of the generated hydrogen atoms will combine to form hydrogen gas and escape, while the other part will be adsorbed on the electrode surface and dissolved into the material, thus realizing the hydrogen charging process of the material. The addition of NaOH makes the oxidation pool in an alkaline environment, and OH - Changes in ion concentration will change the potential distribution on the electrode surface and affect the adsorption and reaction process of hydrogen on the material surface.

[0038] (V) (VI) In addition, unlike the prior art which often uses hydrochloric acid solution for hydrogenation, sulfuric acid is not easy to decompose under acidic conditions and can provide stable H +concentration, so that the hydrogen charging reaction can continue. In contrast, HCl is volatile at high concentrations or high temperatures, which may cause unstable solution components and unstable hydrogen charging. In addition, the pH of 0.5 mol / L sulfuric acid is about 0.3. This strong acidic environment can not only promote the precipitation of hydrogen, but also inhibit the formation of oxide film on the metal surface, ensuring the effective penetration of hydrogen atoms. At the same time, thiourea can also act as a "poisoning agent" and adsorb on the metal surface, effectively slowing down or even preventing atomic hydrogen from polymerizing into hydrogen molecules (H2) and escaping from the cathode surface. Cl in HCl solution - It is easy to cause metal pitting corrosion, especially at high concentrations, which can cause greater damage to equipment; while the sulfuric acid + thiourea system reduces corrosion through the corrosion inhibition of thiourea. Compared with the irritation and volatility of HCl, the concentrated sulfuric acid + thiourea mixed solution is more suitable for laboratory operations.

[0039] It should be noted that in the above examples, 30 mA·cm -2 The test current density is the optimal test current density. This is achieved by using U75V rail base material specimens of the same size and measuring the hydrogen permeation current density at 10 mA·cm -2 , 30mA·cm -2 and 100 mA·cm -2 The results of hydrogen permeation for 1 h were obtained under three experimental conditions. Figure 3-Figure 5 shown.

[0040] from Figure 3-Figure 5 It can be seen that at 10 mA·cm -2 At a low current density of 1 h, the surface damage is slight and effective quantitative damage analysis cannot be performed; at 100 mA·cm -2 (1 h) Excessive hydrogen charging current will cause electric shock to the surface, causing the surface to turn black and making it impossible to conduct hydrogen permeation tests. -2 Under the current density parameter of (1 h), the hydrogen-induced damage morphology such as hydrogen-induced cracks and hydrogen blistering caused by hydrogen penetration into the material is obvious, which is conducive to effective quantitative damage analysis.

[0041] S5: Calculating the apparent hydrogen diffusion coefficient, hydrogen flux and hydrogen concentration on the hydrogen permeation side according to the hydrogen permeation curve.

[0042] In a specific embodiment, the apparent hydrogen diffusion coefficient, hydrogen flux and hydrogen concentration on the hydrogen permeation side are calculated by the following formulae: (1) (2) (3) Where: is the apparent hydrogen diffusion coefficient, cm 2·s -1 ; L is the sample thickness, cm; is the lag time (referring to the anode current density reaching the saturated anode current density I ∞ The time corresponding to 0.63 times of ), s; is the hydrogen flux, mol·cm -2 ·s -1 ; is the saturated anodic current density, A·cm -2 ; n is the number of electrons transferred; F is the Faraday constant (taken as 96485 C·mol -1 ); is the hydrogen concentration on the hydrogen permeation side, mol·cm -3 .

[0043] In the above embodiment, the calculation formula of the apparent hydrogen diffusion coefficient is derived by the following steps: Assume that the hydrogen atom is randomly walking in one-dimensional space, and at each tiny time interval Δt Hydrogen atoms have the same probability of moving left or right Δx After a n After the time interval, the total time t=nΔt ,but: (5) The position of a hydrogen atom is the sum of each displacement, i.e. . Then the mean square displacement is: (6) Define the diffusion coefficient (in one dimension, considering both the left and right directions, so the denominator is 2): (7) but: (8) In three-dimensional space, diffusion is isotropic, and according to the spatial symmetry, the mean square displacement can be expressed as: (9) Since the diffusion in the three directions is equivalent, namely: (10) but: (11) make , which represents the square of the mean square displacement characteristic length of the diffusion of hydrogen atoms in three-dimensional space, can be used to obtain the calculation formula of the apparent hydrogen diffusion coefficient shown in formula (1).

[0044] The calculation formula of the hydrogen flux is derived by the following steps: Faraday's Law: ,but ,in Q is the amount of charge passing through the electrode (unit C); ΔN is the amount of substance reacting (in mol).

[0045] Definition of electric current: ,but ,in I is the current intensity (in A), Q It's in time t The amount of charge passing through the cross section of a conductor (unit: C). Therefore: (12) Flux is defined as the amount of material passing through a unit area per unit time. Assume that the area through which the material passes is A , then the flux of the substance is J .so: (13) In the case of unit area, A =1, the hydrogen flux calculation formula shown in formula (2) can be obtained.

[0046] The calculation formula of the hydrogen concentration on the hydrogen permeation side is derived by the following steps: Fick's first law is: ,but :

[0047] Assume that there are two points on the diffusion path x 1 and x 2, and the corresponding hydrogen atom concentrations are C 1 and C 2. Yes exist x 1 to x Integrate over the interval 2: (14) Points can be obtained: (15) make , ,but: (16) Assumptions x 1=0, C 1=0 (i.e., assuming the initial position and initial concentration are 0), x 2=L ( L is the diffusion distance), then C 2 =C ( C is the hydrogen atom concentration on the hydrogen charging side), the calculation formula for the hydrogen concentration on the hydrogen permeation side shown in formula (3) can be obtained.

[0048] S6: Evaluate the hydrogen damage of each different micro-area sample according to the micro-area structure morphology and the apparent hydrogen diffusion coefficient, hydrogen flux and hydrogen concentration on the hydrogen permeation side.

[0049] In a specific embodiment, when evaluating the hydrogen damage of different micro-area samples: The greater the apparent hydrogen diffusion coefficient, hydrogen flux and hydrogen concentration on the hydrogen permeation side, the higher the possibility of hydrogen damage; Observe whether there are hydrogen-induced cracks and hydrogen bubbles in the micro-region structure morphology, and calculate the degree of hydrogen damage by the following formula: (4) Where: k is the degree of hydrogen damage; α is the weight of hydrogen-induced cracking; x is the hydrogen-induced crack length, nm; β Weight for hydrogen bubbling; y is the major axis length of the hydrogen bubble ellipse, nm.

[0050] In a specific embodiment, a 60 kg / m type U75V rail of Panzhihua Iron and Steel Group is used, and a qualified rail flash weld joint is obtained by a joint preparation process, and this is used as a target rail flash weld joint, and the rail flash weld joint micro-area hydrogen damage test method of the present invention is used to test its micro-area hydrogen damage, which specifically includes the following steps: (1) The target rail flash weld joint is divided into four micro-areas, and the results are shown in Table 1: Table 1 Micro-area division results of U75V rail flash welding joint

[0051] (2) Wire cutting is performed on the target rail flash weld joints in different micro-regions to obtain samples of different micro-regions and obtain the micro-region structure morphology of each sample. The results are as follows: Figure 6 As shown; (3) performing nickel plating treatment on each sample to obtain a nickel-plated sample; In this embodiment, the concentration of the sodium hydroxide solution used for nickel plating is 80 g / L, and the ultrasonic cleaning time is 3 min; the acid etching temperature is 45 ° C, and the acid etching time is 15 s; the electroplating solution used includes 260 g / L NiSO4·6H2O, 45 g / L NiCl2·6H2O, and 40 g / L H3BO3, the electroplating temperature is 60 ° C, the electroplating time is 10 min, and the plating current density is 3 mA·cm -2 ; The nickel layer thickness of the obtained nickel-plated sample is 1 μm; (4) conducting a hydrogen permeation test on the nickel-plated sample in a double electrolytic cell apparatus using a constant current method; In this embodiment, the dual electrolytic cell device is as follows Figure 2 As shown, the test current density is 30 mA·cm -2 After the background current density of the electrochemical workstation is stable, the first hydrogen permeation test is carried out and the hydrogen permeation curve of the anode current density changing with the hydrogen charging time is recorded. The current is 0.0235 A and the voltage is 10 V. The hydrogen charging is stopped after the reaction reaches a steady state. After the first hydrogen permeation test is completed, the solution in the hydrogen charging cell is removed and new hydrogen charging solution is added. When the background current density is stable, the above operation is repeated for the second hydrogen permeation test.

[0052] The hydrogen permeation curve was drawn by comparing the time obtained from the two hydrogen charging times with the background current density data, and the current density was normalized. The results are shown in Figure 7 and Figure 8 The apparent hydrogen diffusion coefficient, hydrogen flux and hydrogen concentration on the hydrogen permeation side of the U75V rail were calculated using the calculation formulas shown in equations (1) to (3). The results are shown in Tables 2, 3 and Fig. 9 shown.

[0053] Table 2 Results of the first hydrogen filling test of U75V rail joint specimens

[0054] Table 3 Results of the second hydrogen charging test of U75V rail samples

[0055] (6) evaluating the hydrogen damage of each different micro-area sample according to the micro-area structure morphology and the apparent hydrogen diffusion coefficient, hydrogen flux and hydrogen concentration on the hydrogen permeation side; From Table 2, Table 3 and Fig. 9 It can be seen that the penetration time and lag time of the first hydrogen penetration are longer than those of the second hydrogen penetration, resulting in the four micro-zones of the U75V welded joint. D app Smaller, and J ∞ In addition, the weld area D app maximum,C 0 is the smallest, indicating that the diffusion rate of hydrogen atoms in this area is the fastest. D app Minimum, C 0 (hydrogen concentration on the hydrogen permeation side) is the largest, indicating that the diffusion rate of hydrogen atoms in this area is the lowest. In the second hydrogen charging experiment, the hydrogen diffusion rates of each micro-area are in the order of weld area > base material area > incomplete normalizing area > complete normalizing area.

[0056] from Figure 6 It can be seen that hydrogen-induced cracks and surface hydrogen bubbles were observed at grain boundaries and internal phase boundaries in the weld zone, complete normalizing zone, incomplete normalizing zone, and parent metal zone. The size of hydrogen bubbles in the incomplete normalizing zone is significantly smaller than that in the complete normalizing zone, and the width of microcracks in the incomplete normalizing zone is less than 1 μm, which is narrower than the width of microcracks in the complete normalizing zone. The hydrogen-induced damage in the parent metal zone is equivalent to that in the incomplete normalizing zone, which is manifested as hydrogen-induced cracks distributed along the pearlite grain boundaries. In addition, the surface of the sample after hydrogen penetration in the weld zone is smooth and flat, with only a limited number of hydrogen bubbles and a small number of microcracks with a length of 10 to 20 μm.

[0057] In the flash welded joints of U75V rails, hydrogen-induced cracks are the main form of hydrogen damage, followed by hydrogen blistering. Therefore, when evaluating the degree of hydrogen damage, a weight of 0.8 is applied to the length of hydrogen-induced cracks and a weight of 0.2 is applied to the length of the major axis of the hydrogen blister ellipse. The morphology of hydrogen damage in each micro-area is shown in Figure 2. Fig.10 As shown, the degree of hydrogen damage calculated according to formula (4) is shown in Table 4: Table 4 Calculation results of hydrogen damage degree in each micro-area

[0058] from Fig.10 It can be seen from Table 4 that the degree of hydrogen damage in each micro-area is in the order of complete normalizing area > incomplete normalizing area > parent material area > weld area. The apparent hydrogen diffusion rate of each micro-area measured experimentally is in the order of weld area > parent material area > incomplete normalizing area > complete normalizing area. The value of the apparent hydrogen diffusion rate reflects the degree of hydrogen capture in the steel. The smaller the hydrogen diffusion coefficient, the more hydrogen is trapped in the steel, which is more likely to cause hydrogen damage. The hydrogen damage results of the hydrogen damage degree evaluation are consistent with the theoretical hydrogen damage of the apparent hydrogen diffusion coefficient measured experimentally, indicating its accuracy in evaluating the hydrogen damage of the U75V rail weld joint.

[0059] In summary, the present invention can accurately test the micro-area hydrogen damage of the rail flash weld joint. Compared with the prior art, the present invention has significant progress.

[0060] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for testing micro-area hydrogen damage of rail flash weld joints, characterized in that: The following steps are involved: S1: obtaining a target rail flash weld joint, and dividing the target rail flash weld joint into four micro-areas, wherein the four micro-areas include a weld area, a complete normalizing area, an incomplete normalizing area, and a base material area; S2: Wire cutting is performed on the target rail flash weld joints of different micro-regions to obtain samples of different micro-regions, and the micro-region structure morphology of each sample is obtained; S3: performing nickel plating treatment on each sample to obtain a nickel-plated sample; S4: performing a hydrogen permeation test on the nickel-plated sample in a double electrolytic cell device using a constant current method to obtain a hydrogen permeation curve of current density changing with hydrogen charging time during the test; S5: calculating the apparent hydrogen diffusion coefficient, hydrogen flux and hydrogen concentration on the hydrogen permeation side according to the hydrogen permeation curve; S6: Evaluate the hydrogen damage of each different micro-area sample according to the micro-area structure morphology and the apparent hydrogen diffusion coefficient, hydrogen flux and hydrogen concentration on the hydrogen permeation side.

2. The method for testing micro-area hydrogen damage of rail flash weld joints according to claim 1, characterized in that: In step S1, when dividing the micro-areas, the weld is used as a reference, and the areas with finer grain structures on both sides of the weld are divided into complete normalizing areas, and the areas with coarser grain structures on both sides of the weld are divided into incomplete normalizing areas, and the side adjacent to the incomplete normalizing area and away from the weld is divided into a parent material area; the average grain size of the coarser grain structure is larger than the average grain size of the finer grain structure.

3. The method for testing micro-area hydrogen damage of rail flash weld joints according to claim 1, characterized in that: In step S2, the microstructure morphology of each sample is obtained by using an electron backscatter diffraction scanning electron microscope and an optical microscope.

4. The method for testing micro-area hydrogen damage of rail flash weld joints according to claim 1, characterized in that: In step S3, the nickel plating treatment of the sample specifically includes the following sub-steps: S31: ultrasonically cleaning the sample in a sodium hydroxide solution, and then washing and drying the sample with deionized water; S32: etching the sample dried in step S31 with a concentrated hydrochloric acid solution, and then washing and drying with deionized water; S33: nickel-plating the sample dried in step S32, and then washing and drying with deionized water to obtain the nickel-plated sample.

5. The method for testing micro-area hydrogen damage of rail flash weld joints according to claim 4, characterized in that: In step S31, the concentration of the sodium hydroxide solution is 80 g / L, and the ultrasonic cleaning treatment time is 3 min; in step S32, the acid etching temperature is 45° C., and the acid etching time is 15 s.

6. The method for testing micro-area hydrogen damage of rail flash weld joints according to claim 4, characterized in that: In step S33, when nickel plating is performed, the electroplating solution used includes 260 g / L NiSO4·6H2O, 45 g / L NiCl2·6H2O, and 40 g / L H3BO3, the electroplating temperature is 60 °C, the electroplating time is 10 min, and the plating current density is 3 mA·cm -2 .

7. The method for testing micro-area hydrogen damage of rail flash weld joints according to claim 1, characterized in that: In step S4, the dual electrolytic cell device includes an oxidation cell, a hydrogen charging cell, an electrochemical workstation and a constant potential instrument, the oxidation cell and the hydrogen charging cell are both connected to the nickel-plated sample, and the working electrode of the electrochemical workstation and the negative electrode of the constant potential instrument are both connected to the nickel-plated sample; the oxidation cell serves as an anode cell, the platinum electrode therein is connected to the auxiliary electrode of the electrochemical workstation, and the reference electrode therein is connected to the reference electrode of the electrochemical workstation; the hydrogen charging cell serves as a cathode cell, the platinum electrode therein is connected to the positive electrode of the constant potential instrument.

8. The method for testing micro-area hydrogen damage of rail flash weld joints according to claim 7, characterized in that: In step S4, when the hydrogen permeation test is performed, the electrolyte in the oxidation tank is a 4 g / L sodium hydroxide solution, the hydrogen charging liquid in the hydrogen charging tank is a mixed solution of 0.5 mol / L concentrated sulfuric acid and 2 g / L thiourea, and the test current density is 30 mA cm -2 .

9. The method for testing micro-area hydrogen damage of rail flash weld joints according to claim 1, characterized in that: In step S5, the apparent hydrogen diffusion coefficient, hydrogen flux and hydrogen concentration on the hydrogen permeation side are calculated by the following formulae respectively: (1) (2) (3) Where: is the apparent hydrogen diffusion coefficient, cm 2 ·s -1 ; L is the sample thickness, cm; is the lag time, s; is the hydrogen flux, mol·cm -2 ·s -1 ; is the saturated anodic current density, A·cm -2 ; n is the number of electrons transferred; F is the Faraday constant; is the hydrogen concentration on the hydrogen permeation side, mol·cm -3 .

10. The method for testing micro-area hydrogen damage of rail flash weld joints according to any one of claims 1 to 9, characterized in that: In step S6, when evaluating the hydrogen damage of each different micro-area sample: The greater the apparent hydrogen diffusion coefficient, hydrogen flux and hydrogen concentration on the hydrogen permeation side, the higher the possibility of hydrogen damage; Observe whether there are hydrogen-induced cracks and hydrogen bubbles in the micro-region structure morphology, and calculate the degree of hydrogen damage by the following formula: (4) Where: k is the degree of hydrogen damage; α is the weight of hydrogen-induced cracking; x is the hydrogen-induced crack length, nm; β Weight for hydrogen bubbling; y is the major axis length of the hydrogen bubble ellipse, nm.

Citation Information

Patent Citations

  • Device and method of testing hydrogen diffusion coefficient of steel and iron material at low temperature

    CN102809525A

  • Device and method for measuring hydrogen diffusion coefficient of microcell of welded joint and application of device and method for measuring hydrogen diffusion coefficient of microcell of welded joint

    CN114563341A

  • Insulating material hydrogen atom diffusion performance evaluation method and system

    CN115078482A